Students’ entrepreneurship interest and cognitive learning outcomes: Effectiveness of biodiversipreneurship - Nur Hayati; Lina Arifah Fitriyah (Universitas Negeri Jakarta, 2021)
This study used a quantitative method with a pre-experimental design, model of one group pretest-posttest design. The purpose of this study was to determine the effectiveness of the biodiversipreneurship learning method on students’ learning outcomes and entrepreneurship interest. This research was applied to the Biotechnology course with the sample consisting of 15 students of Natural Science Education department of UNHASY Jombang in the fifth semester of 2018 class. The research instrument included a learning outcome assessment sheet and entrepreneurship interest questionnaires. Data analysis was done quantitatively descriptively with independent sample t test. The t-test analysis on learning outcomes in the form of pretest-posttest scores and interest in entrepreneurship shows the significance value of 0.000 or ≤ 0.05. Thus, it can be concluded that biodiversipreneurship learning method is effective in increasing students’ learning outcomes and interest in entrepreneurship.